The role of incoherence: postcolonial pedagogy and theology in the narrative of the conquest of the Nueva corónica y buen gobierno - Lamana, Gonzalo (2020)
This essay studies some aspects of the narrative of the conquest of Guaman Poma de Ayala’s Nueva corónica y buen gobierno that have received limited scholarly attention. Its main argument is that the Andean author’s goal was to alter the way in which readers gave meaning to the world in which they lived. To that end, he adopted a pedagogical strategy: he confronted the readers with apparent incoherences and historical absurdities, to surprise them and have them ponder, hesitate and, fnally, realize that it was the premises they held about reality that made those elements seem strange, absurd, or incoherent, not the elements themselves. That is, they were riddles, means for a strategy with decolonial ends.